Variability in vertebral numbers does not contribute to sexual size dimorphism, interspecific variability, or phenotypic plasticity in body size in geckos (Squamata: Gekkota: Paroedura). Issue 4 (18th April 2018) - Kratochvíl, Lukáš; Kubička, Lukáš; Vohralík, Martin; Starostová, Zuzana
Abstract: Body size is a fundamental trait correlated with nearly every aspect of animal life. It is influenced by numerous genetic and non‐genetic factors. Despite its central importance, proximate mechanisms of intra‐ and interspecific variability in body size are still not well understood even in such a largely studied group as reptiles. For our study, we concentrated on the gecko species Paroedura picta . We investigated whether differences in sexual size dimorphism and in final and asymptotic snout‐vent length (induced by a range of incubation and rearing temperatures) are correlated with differences in the number of presacral vertebrae. Moreover, we tested whether changes in this number were associated with evolutionary changes in sexual size dimorphism and body size in the genus Paroedura . We found that the variation in the number of presacral vertebrae is very limited both intra‐ and interspecifically, ranging between 26 and 28 vertebrae with most individuals possessing the modal number of 27. We conclude that changes in the number of vertebrae do not contribute to developmental plasticity or evolutionary changes in body size nor, in contrast to some other squamate lineages, to sexual size dimorphism. GRAPHICAL ABSTRACT: The variation in the number of presacral vertebrae is limited both intra‐ and interspecifically in the Paroedura geckos. Changes in the vertebral numbers do not contribute to changes in body size and sexual size dimorphism.